Genetic Diversity and Natural Selection of Plasmodium vivax Duffy Binding Protein-II From China-Myanmar Border of Yunnan Province, China - Tian-Qi Shi (Frontiers Media S.A., 2021)
Malaria incidence has declined dramatically over the past decade and China was certified malaria-free in 2021. However, the presence of malaria in border areas and the importation of cases of malaria parasites are major challenges for the consolidation of the achievements made by China. Plasmodium vivax Duffy binding protein (PvDBP) performs a significant role in erythrocyte invasion, and is considered a promising P. vivax vaccine. However, the highly polymorphic region of PvDBP (PvDBP-II) impedes the development of blood-stage vaccine against P. vivax. In this study, we investigated the genetic diversity and natural selection of PvDBP-II among 124 P. vivax isolates collected from the China-Myanmar border (CMB) in Yunnan Province, China, during 2009–2011. To compare genetic diversity, natural selection, and population structure with CMB isolates, 85 pvdbp-II sequences of eastern Myanmar isolates were obtained from GenBank. In addition, global sequences of pvdbp-II were retrieved from GenBank to establish genetic differentiation relationships and networks with the CMB isolates. In total, 22 single nucleotide polymorphisms reflected in 20 non-synonymous and two synonymous mutations were identified. The overall nucleotide diversity of PvDBP-II from the 124 CMB isolates was 0.0059 with 21 haplotypes identified (Hd = 0.91). The high ratio of non-synonymous to synonymous mutations suggests that PvDBP-II had evolved under positive selection. Population structure analysis of the CMB and eastern Myanmar isolates were optimally grouped into five sub-populations (K = 5). Polymorphisms of PvDBP-II display that CMB isolates were genetically diverse. Mutation, recombination, and positive selection promote polymorphism of PvDBP-II of P. vivax population. Although low-level genetic differentiation in eastern Myanmar was identified along with the more effective malaria control measures, the complexity of population structure in malaria parasites has maintained. In conclusion, findings from this study advance knowledge of the understanding of the dynamic of P. vivax population, which will contribute to guiding the rational design of a PvDBP-II based vaccine.